Duration of Perioperative Chemotherapy in Locally Advanced Gastric Cancer: A “Less Is More” Question When ypN0 Is Achieved - Liu, Zining; Wang, Yinkui; Shan, Fei; Ying, Xiangji; Zhang, Yan; Li, Shuangxi; Jia, Yongning; Miao, Rulin; Xue, Kan; Li, Zhemin; Li, Ziyu; Ji, Jiafu (Frontiers in Oncology, 2021)
Backgrounds: Perioperative chemotherapy (PEC) and Neoadjuvant chemotherapy (NAC) have become a vital part of locally advanced gastric cancer (LAGC) treatment, but the optimal duration of PEC has not been studied. The aim of this study was to demonstrate the possibility of duration reduction of PEC in the adjuvant chemotherapy (AC) phase for ypN0 patients. Methods: We included LAGC patients who achieved ypN0 after NAC in our institution from 2005 to 2018. The risk/benefit of AC and other covariates were majorly measured by overall survival (OS) and progression-free survival (PFS). We developed a survival-tree-based model to determine the optimal PEC duration for ypN0 patients in different classes. Results: 267 R0 resection patients were included. There were 55 patients who did not receive AC. The 5-year OS was 74.34% in the non-AC group and 83.64% in the AC group with a significant difference (P=0.012). Multivariate Cox regression revealed that both AC (AC vs. non-AC: HR, 0.49; 95%CI, 0.27-0.88; P=0.018) and ypT stages (ypT3-4 vs. ypT0-2: HR, 2.00; 95%CI, 1.11–3.59; P=0.021) were significant protective/risk factors on patients OS and PFS. A decision tree model for OS indicated an optimal 4-6 cycles of PEC which was recommended for ypT0-2N0 patients, while a minimum of 5 PEC cycles was recommended for ypT3-4N0 patients. Conclusion: AC treatment is still necessary for ypN0. The duration reduction could be applied for the ypT0-2N0 stage patients but may not be suitable for higher ypT stages and beyond. A multicenter-based study is required.